2017
DOI: 10.1162/opmi_a_00008
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Modulation Structure of Infant-Directed Speech

Abstract: The temporal modulation structure of adult-directed speech (ADS) is thought to be encoded by neuronal oscillations in the auditory cortex that fluctuate at different temporal rates. Oscillatory activity is thought to phase-align to amplitude modulations in speech at corresponding rates, thereby supporting parsing of the signal into linguistically relevant units. The temporal modulation structure of infant-directed speech (IDS) is unexplored. Here we compare the amplitude modulation (AM) structure of IDS record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
151
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(172 citation statements)
references
References 40 publications
20
151
1
Order By: Relevance
“…Table 1 provides a summary of these 4 temporal bands and the boundaries. It is important to note that, as shown in the spectral PCA, the results of the temporal PCA were highly similar to studies of CDS by Leong and Goswami [8] and to related studies of IDS [9]. Further, overall frequencies showed higher consistency across genres.…”
Section: Spectral Pcasupporting
confidence: 80%
See 2 more Smart Citations
“…Table 1 provides a summary of these 4 temporal bands and the boundaries. It is important to note that, as shown in the spectral PCA, the results of the temporal PCA were highly similar to studies of CDS by Leong and Goswami [8] and to related studies of IDS [9]. Further, overall frequencies showed higher consistency across genres.…”
Section: Spectral Pcasupporting
confidence: 80%
“…Indeed, speech-based modelling has revealed that IDS shows significant extra modulation energy in the delta band compared to adult-directed speech, contributing to its high rhythmicity [9]. The current data also map nicely to the Plomp and Levelt [55] modeling of the dissonance curve for spectral frequency (i.e., "pitch").…”
Section: Phase Synchronization In Both Modelssupporting
confidence: 65%
See 1 more Smart Citation
“…Accurate perception of speech prosody is fundamental to the development of a mental lexicon of word forms in infancy and childhood, across languages (Jusczyk et al, 1999, Mehler et al, 1988). Further, recent analyses of the amplitude modulation structure of Australian English infant-directed speech (IDS) show a modulation peak at 2 Hz, the “prosodic rate” (see Leong, Kalashnikova, Burnham, & Goswami, 2014), not at 4–6 Hz, the modulation peak found for adult-directed speech (ADS, see Greenberg, Carvey, Hitchcock, & Chang, 2003). These different modulation peaks imply that early in development, accurate encoding of low frequency envelopes (delta band) could play a crucial role in setting up a phonological lexicon (Leong & Goswami, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The AM tiers were arranged hierarchically in the speech signal, with delta (2 Hz) as the master oscillator. Indeed, analyses of infant-directed speech (IDS) reveal that the greatest energy in the speech signal is in the delta band, suggestive of a core role for slow temporal modulations in initial language learning (Leong et al, 2014). The dominance of energy modulations in the delta band also provides an interesting contrast to adult-directed speech (ADS), in which theta band modulations dominate (~ 5 Hz).…”
Section: Introductionmentioning
confidence: 99%